(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study was carried out to determine the modern office technology competencies expected of office technology and management (OTM) graduate workers by supervisors in Delta State. The study was guided by two research questions and two hypotheses tested at 0.05 level of significance. The respondents consisted of 142 supervisors, made up of 74 heads of department and directors of government establishments, and 68 managers and directors of private establishments in the study area. Survey research design was used to conduct the study. A 28-items questionnaire was used to collect data from respondents, which was used for the research. The instrument was validated by experts and had a total Cronbach Alpha reliability coefficient of 0.77. Mean and standard deviations were used to answer the research questions, while t-test was used to test the null hypotheses. The findings of the study indicated that the supervisors, who are employers as well, very much expect information processing competencies from the OTM graduate workers. The extent of supervisors’ expectations of information processing competencies did not differ significantly based on the mean ratings of male and female supervisors of OTM graduates in government and private establishments. The findings also reveal that supervisors expect much communication competencies from the OTM graduate workers. The extent of supervisors’ expectations of communication competencies did not differ significantly based on the mean ratings of experienced and inexperienced supervisors of OTM graduate workers in government and private establishments. The findings imply that various modern office technology competencies are much needed in government and private establishments irrespective of experience and gender of the supervisors. Hence, the identified competencies need to be emphasized in curriculum practice, training and development for future office technology and management workers. Based on the findings and the implications, it was recommended among other things that, curriculum planners, business and OTM education lecturers should ensure that the competencies required for modern office technologies are entrenched in the school curriculum and taught in the institutions